Breaking blue ebook - Egan, Timothy (2011)
“No one who enjoys mystery can fail to savor this study of a classic case of detection.”  —TONY HILLERMAN   On the night of September 14, 1935, George Conniff, a town marshal in Pend Oreille County in the state of Washington, was shot to death.  A lawman had been killed, yet there seemed to be no uproar, no major investigation.  No suspect was brought to trial.  More than fifty years later, the sheriff of Pend Oreille County, Tony Bamonte, in pursuit of both justice and a master’s degree in history, dug into the files of the Conniff case—by then the oldest open murder case in the United States.  Gradually, what started out as an intellectual exercise became an obsession, as Bamonte asked questions that unfolded layer upon layer of unsavory detail.                 In Timothy Egan’s vivid account, which reads like a thriller, we follow Bamonte as his investigation plunges him back in time to the Depression era of rampant black-market crime and police corruption.  We see how the suppressed reports he uncovers and the ambiguous answers his questions evoke lead him to the murder weapon—missing for half a century—and then to the man, an ex-cop, he is convinced was the murderer.                 Bamonte himself—a logger’s son and a Vietnam veteran—had joined the Spokane police force in the late 1960s, a time when increasingly enlightened and educated police departments across the country were shaking off the “dirty cop” stigma.  But as he got closer to actually solving the crime, questioning elderly retired members of the force, he found himself more and more isolated, shut out by tight-lipped hostility, and made dramatically aware of the fraternal sin he had committed—breaking the blue code.                 Breaking Blue is a gripping story of cop against cop.  But it also describes a collision between two generations of lawmen and two very different moments in our nation’s history.